2015
DOI: 10.1016/j.cemconres.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced properties of graphene/fly ash geopolymeric composite cement

Abstract: This paper reports for the first time the incorporation of in-situ reduced graphene oxide (rGO) into geopolymers. The resulting rGO-geopolymeric composites are easy to manufacture and exhibit excellent mechanical properties. Geopolymers with graphene oxide (GO) concents of 0.00, 0.10, 0.35 and 0.50% by weight were fabricated. The functional groups, morphology, void filling mechanisms and mechanical properties of the composites were determined. The Fourier transform infrared (FTIR) spectra revealed that the alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(80 citation statements)
references
References 31 publications
2
69
0
5
Order By: Relevance
“…Recently, the incorporation of rGO in geopolymer composites showed that rGO particles enhance the flexural strength, Young's modulus and toughness of the geopolymeric composites because they display a 2-dimensional structure and strong chemical bonding with the matrix. Further, the addition of low amounts of rGO sheets into geopolymers improved the mechanical properties and reduced the overall porosity of the composite specimens [29,30]. To achieve this potential material enhancement, the development of an efficient and capable method for the mass production of graphene for industrial applications has attracted increased attention.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the incorporation of rGO in geopolymer composites showed that rGO particles enhance the flexural strength, Young's modulus and toughness of the geopolymeric composites because they display a 2-dimensional structure and strong chemical bonding with the matrix. Further, the addition of low amounts of rGO sheets into geopolymers improved the mechanical properties and reduced the overall porosity of the composite specimens [29,30]. To achieve this potential material enhancement, the development of an efficient and capable method for the mass production of graphene for industrial applications has attracted increased attention.…”
Section: Introductionmentioning
confidence: 98%
“…Geopolymers are prepared by an exothermic dehydration reaction, and the ratio of the reactants significantly influences their structure integrity [17][18][19], causing significant variations in the distribution of sizes of pores. Most pores in geopolymers have diameters within the range of 10-1000 nm [20][21][22][23][24][25] time-consuming [26][27]; so measurements regarding the hydraulic conductivity of geopolymers are rarely made.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [16] found the incorporation of 0.03% graphene oxide (GO) increased the tensile and compressive strength of the cement paste by more than 40%, and the degree of hydration of GO–cement composites was promoted. Saafi et al [17] observed that a 134% and 56% enhancement in flexural strength and flexural toughness of graphene–geopolymer composites were obtained for the addition of 0.35 wt % reduced graphene oxide (rGO). Other researchers have incorporated graphene or graphene oxide into cement-based composites as a filler material to enhance the flexural strength by 40%–60% and the compressive strength by more than 10% [18,19,20].…”
Section: Introductionmentioning
confidence: 99%